Effects of Sodium/Glucose Cotransporter 2 (SGLT2) Inhibitors on Cardiac Imaging Parameters: A Systematic Review and Meta-analysis of Randomized Controlled Trials - Wee, CF (Korean Society of Echocardiography, 2022)
10.4250/jcvi.2021.0159